Edukasi Kewajiban Perpajakan dan Pemanfaatan Sistem Informasi Perpajakan untuk Meningkatkan Generasi Sadar Pajak [Tax Obligation Education and the Utilization of Tax Information Systems to Develop a Tax-Conscious Generation] - Novalina Arifianti; Heni Agustina; Zanuba Ziyadatul Latifah (Indonesia Berdaya, 2026)
State revenue from taxes has not yet reached its full potential due to non-compliance among taxpayers. Taxpayer compliance can be influenced by the low level of public understanding regarding tax obligations and tax information systems. To create a tax-conscious generation, tax counseling activities are necessary. The purpose of this Community Service Program (PKM) is to improve the understanding of students at SMAN 1 Bangsal regarding tax obligations and tax information systems in order to increase their awareness of their tax responsibilities. The PKM activities were carried out using a counseling method for 11th-grade students of SMAN 1 Bangsal by the PKM team from the Accounting Study Program of UNUSA. The implementation method consisted of three stages: preparation, implementation, and evaluation. The results after the counseling show an increase in students’ knowledge about taxation. The conclusion of this PKM activity is that tax socialization can enhance the understanding of SMAN 1 Bangsal students about tax obligations and tax information systems, thereby helping to create a tax-conscious generation. Abstrak. Penerimaan negara berasal dari pajak belum maksimal akibat wajib pajak yang tidak patuh. Kepatuhan  wajib  pajak dapat disebabkan oleh tingkat pemahaman masyarakat tentang kewajiban perpajakan dan system informasi perpajakan rendah. Untuk menciptakan generasi sadar pajak perlu diadakan penyuluhan. Tujuan PKM adalah meningkatkan pemahaman siswa SMAN 1 Bangsal terhadap kewajiban perpajakan dan system informasi perpajakan agar meningkatkan kesadaran tentang kewajiban perpajakan mereka.  Kegiatan  PKM dilakukan  dengan  metode penyuluhan kepada  siswa  kelas XI SMAN 1 Bangsal oleh tim PKM prodi Akuntansi UNUSA. Metode  pelaksanaan  yang  digunakan  terdiri dari tiga tahap, yaitu: tahap persiapan, tahap pelaksanaan, dan tahap evaluasi. Hasil yang didapat setelah penyuluhan adalah pengetahuan siswa tentang pajak meningkat. Kesimpulan dari    kegiatan  PKM ini adalah sosialisasi pajak dapat meningkatkan pemahaman siswa SMAN 1 Bangsal tentang kewajiban perpajakan dan system informasi perpajakan sehingga dapat menciptakan  generasi sadar pajak.